The Effect of Brand Image and Price on Tourist Purchasing Decisions Choosing The Westin Resort Nusa Dua Bali as a Mice Venue - Wedari, Ni Kadek Maedha; Pitanatri, Putu Diah Sastri; Wiartha, Nyoman Gede Mas (PT FORMOSA CENDEKIA GLOBAL, 2024)
The tourism industry has great potential in generating foreign exchange and improving the welfare of the community. MICE (Meeting, Incentive, Convention, and Exhibition) is a rapidly growing sector in this industry. The MICE industry in Indonesia has been severely impacted by the COVID-19 pandemic, with many events postponed or canceled, affecting related economic sectors. Recovery of the sector requires strategies to adapt to the